Analysis of the Role of Bank Indonesia's Leading Entrepreneurship Initiative (WUBI) in Increasing Competitiveness in the Digital Era, Case Study of MSMEs Representatives of Bank Indonesia North Sumatra - Noor, Atikah; Yafiz, Muhammad; Dharma, Budi (Jurnal Manajemen Bisnis, 2024)
Bank Indonesia has a program called Wirausaha Binaan Unggulan Bank Indonesia (WUBI) which focuses on improving the competitiveness of MSMEs in the digital era. This research analyzes the role of WUBI in improving the competitiveness of MSMEs with a case study of MSMEs assisted by Bank Indonesia Representative of North Sumatra. Qualitative research methods were used with primary data obtained through in-depth interviews with fostered MSMEs. The results showed that WUBI plays an important role in improving the competitiveness of MSMEs in the digital era through: (1) capacity building through training and mentoring, (2) business and marketing network development, and (3) utilization of digital technology for business efficiency and effectiveness. In conclusion, the WUBI Program has a positive impact on MSME competitiveness, increasing sales, profitability, and market access. The program also helps MSMEs improve their financial management, digital marketing, and product development skills.